A Critical Analysis of The Movie Kartini About Feminism Directed by Hanung Bramantyo - Tania Priscila; Wikanengsih (JLER (Journal of Language Education Research), 2024)
Kartini is an Indonesian emancipation and feminism figure. One of the movies we talk about is Kartini directed by Hanung Bramantyo and Dian Sastro as Kartini, is one of the most popular movies in Indonesia. It is a movie of the era of the "Kartini" which is based on a film of the same title. The goal of this study is to find the quality of an object analyzed in a form of description using the data gained. The qualitative descriptive method is used for this research. The main purpose of this research is want to using movie as a media can be used as a tool to describe in detail what happened at that time to people in the future. Emotion and feelings also played parts that supported the situation in the movie. Media’s role is important so that people can see how big Kartini’s struggles to fight the rights for women in education. In the hopes that this movie can be remembered in woman’s minds, so that woman nowadays can fight and enthusiast in pursuing education. According to data analysis shows that Kartiani is real Indonesian figure. There are some Kartini’s struggles which gave much impact to women until now. It inspires woman to not giving up in achieving their education and also get the same right to speak up. As a woman, it is truly an obligation to obey their husband, but their husband should respect their wife’s opinion as well.